Bifurcation analysis of steady-state flows in the lid-driven cavity. (7th November 2016) - Nuriev, A N; Egorov, A G; Zaitseva, O N
Abstract: The paper is devoted to the study of the non-uniqueness issues of a steady-state flow in the square lid-driven cavity. A range 0 < Re < 20000 of Reynolds numbers is considered in which a numerical bifurcation analysis is carried out. The analysis allows us to localize several branches of the steady-state solution and also to investigate their stability.